2010
DOI: 10.1007/s10826-010-9404-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Learning Experience and Adolescent Anxiety: A Cross-Cultural Comparison Between Japan and England

Abstract: The main aim of this study was to compare the frequency of anxiety symptoms among adolescents in Japan and England, and to examine the association between early learning experiences and anxiety symptoms. A total of 299 adolescents (147 from England and 152 from Japan), aged 12 to 17 years were investigated. Results showed that adolescents in England reported significantly higher levels of anxiety symptoms than adolescents in Japan. For early learning experiences, no significant differences emerged between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some countries, like Japan, do not often discuss minds or mental states openly or explain their actions. For example, a study reported that Japanese parents reported more reinforcement to non-anxiety related symptoms than anxiety related symptoms (Essau, Ishikawa, & Sasagawa, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some countries, like Japan, do not often discuss minds or mental states openly or explain their actions. For example, a study reported that Japanese parents reported more reinforcement to non-anxiety related symptoms than anxiety related symptoms (Essau, Ishikawa, & Sasagawa, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study has several strengths. First, participants were included from a wide geographical area ensuring that the impact of the pandemic on the level of anxiety among AYA is studied across different cultures and sociodemographic backgrounds [ 30 ]. In addition, the study assessed the impact of country level factors on anxiety levels.…”
Section: Discussionmentioning
confidence: 99%